Controlling of conduction mechanism and electronic parameters of silicon-metal junction by mixed Methylene Blue/2?-7?-dichlorofluorescein - Soylu, M.; Al-Hartomy, Omar A.; Al Said, Said A. Farha; Al-Ghamdi, Ahmed A.; Yahia, I. S.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2013)
Al/p-Si junction based on Organic Mixed Layer (OML) Methylene Blue (MB) and 2'-7'-dichlorofluorescein (DCF) was fabricated and the current voltage (I-V) and the capacitance voltage measurements of the structure have been obtained at room temperature. This combination resulted in both a good rectifying behavior and low leakage current. The characteristic parameters of the structure such as barrier height, ideality factor, interface states density and series resistance were determined from the electrical measurements. Also, Cheung functions and Norde method were used to evaluate the I-V characteristics and to obtain the characteristic parameters of the Schottky contact. High-low frequency capacitance voltage characteristics have been observed to have a maximum. The maximum value of the capacitance is decreased with increasing frequency. The higher values of capacitance at low frequencies were attributed to interface states and the excess capacitance resulting from the interface states in equilibrium with the Si that can follow the alternating current signal. The J-V curves in the reverse direction are taken and interpreted via both Schottky and Poole-Frenkel effects. Poole-Frenkel effect was found to be dominant in the reverse direction. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current-Voltage; Electrical Characteristics; Semiconductor Contact; Barrier Height; Photovoltaic Properties; Series Resistance; Interface States; Organic-Compound; Schottky Diodes; Gaas Diode